Easy, Quick, and Reproducible Sonochemical Synthesis of Cuo Nanoparticles - Ramírez-Pastén, S; Ramírez-Pastén, S (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Copper oxide nanoparticles (CuO NPs) were synthesized in air by reducing copper (II) sulfate pentahydrate salt (CuSO(4)5H(2)O) in the presence of sodium borohydride. The reaction was stabilized with Hexadecyltrimethylammonium bromide (CTAB) in a basic medium and using ultrasound waves. Different molar ratios of CTAB:Cu2+ and NaBH4:Cu2+ were explored, to optimize the synthesis conditions, and to study the stability, size, and Zeta potential of the colloidal suspension. Optimum conditions to generate spherical, stable, and monodispersed nanoparticles with hydrodynamic diameters of 36 +/- 1.3 nm were obtained, using 16 mM CTAB and 2 M NaBH4 (molar ratios Cu2+:CTAB:NaBH4 of 1:6:10). X-ray diffraction (XRD) was implemented, and a monoclinic CuO crystal system was formed. This demonstrated a monoclinic crystal system corresponding to CuO. The diffraction peaks were identified and confirmed according to their selected area electron diffraction (SAED) patterns.